Media Coverage and Stock Returns on the London Stock Exchange, 1825–70 - Turner, John D; Ye, Qing; Walker, Clive B (Review of Finance, 2018)
Abstract News media plays an important role in modern financial markets. In this article, we analyze the role played by the news media in an historical financial market. Using The Times’s coverage of companies listed on the London stock market between 1825 and 1870, we examine the determinants of media coverage in this era and whether media coverage affected returns. Our main finding is that a media effect mainly manifests itself after the mid-1840s and that the introduction of arm’s-length ownership along with markedly increased market participation was the main reason for the emergence of this media effect.